Prevalence and factors associated with behavioral disorders in children with chronic health conditions - Budi Santoso Adji; Soetjiningsih Soetjiningsih; Trisna Windiani (Paediatrica Indonesiana, 2010)
Background Patients suffering from chronic health conditions are compelled to strive to adjust in their communities. As a result, changes in their physical and psychosocial states are likely to occur. Several studies have described the prevalence of behavioral disorders in such patients. Pediatric Symptom Checklist (PSC) is a screening tool to detect behavioral disorders in children with chronic illness.Objective To determine the prevalence of and factors associated with behavioral disorders in children with chronic health conditions.Methods A cross sectional study was conducted on 4 to 14 year-old-children with chronic diseases in out-patient clinic, Sanglah Hospital from October to December 2008. PSC-17 was used to screen the presence of behavioral disorders. Bivariate analysis and logistic regression were used for analysis.Results One hundred and four children were included in this study. The prevalence of behavioral disorder based on PSC-17 score â‰¥ 15 was 37.5%. The study showed that duration of illness of more than 3 years had significant correlation with behavioral disorders, compared with the group of 3 month â€“ 3 years duration of illness (OR 3.30, 95% CI 1.33 to 8.22, P = 0.010}.Conclusions Prevalence of behavioral disorders in children with chronic health condition is 37.5%. The duration of illness contributes to the manifestation of behavioral disorders in children with chronic health conditions. [Paediatr Indones. 2010;50:1-5].